Self-Concept Profiles in Lower Secondary Level – An Explanation for Gender Differences in Science Course Selection? - Saß, Steffani; Kampa, Nele (Frontiers in Psychology, 2019)
One of the most powerful determinants for course selection in upper secondary level is undoubtedly students´ self-concept. Students with high self-concept in a domain are more likely to select a course in the respective domain. However, according to the dimensional comparison theory the formation of self-concept also includes comparison processes with self-concept in other domains. Regarding gender, girls are less likely to choose physics and hold lower STEM self-concepts as well as aspirations towards STEM careers than boys. In Germany, students choose specific academic tracks in Grade 10 to follow during upper secondary school. The academic track choice goes in hand with choosing advanced courses. This choice entails if students want to pursue STEM subjects. We have adopted the person-centered approach latent profile analysis (LPA) to investigate the pattern of students´ self-concepts across the five domains mathematics, biology, reading, English, and physics. Furthermore, we investigated how those patterns influence educational choices for or against science subjects in upper secondary school in Germany. Based on a sample of 1658 students, we tested whether distinct profiles of self-concept in different domains in Grade 8 predict gendered science course selection in Grade 10 as well as career aspiration in science. LPA yielded four distinct profiles of self-concept that differed in level and shape: high math, high verbal, general low, and general high. These profiles were equivalent across gender. Gender differences were manifested in the relative distribution across the four profiles: girls were more present in the profiles overall low and high verbal-related self-concept and boys in the profiles overall high and high math-related self-concept. The profiles differ regarding abilities, choice of science course in upper secondary level and science aspiration.